Early history of the study of bone growth (1722-1875) - Bartoníček, Jan; Naňka, Ondřej (International orthopaedics, 2024)
INTRODUCTION: Bone growth is a fascinating process, primarily due to its complexity. Equally engaging is the history of its study, which, however, remains unknown to most anatomists and surgeons. MATERIALS AND METHODS: A literature search was performed in original publications and historical sources. RESULTS: The early history of bone growth study may be divided into two periods. Firstly, the experimental one, between 1722 and 1847, which consisted in the study of bone growth by the drilling of benchmark holes into the diaphysis, and examination of growing bones in madder-fed animals. In the course of one century, four French scientists (Henri-Louis Duhamel du Monceau, Marie-Jean-Pierre Flourens, Gaspard Auguste Brullé and Frédéric Léopold Hugueny) and one British researcher (John Hunter) proved experimentally that the longitudinal growth of long bones occurred only at its epiphyseal ends and their final shape resulted from apposition and resorption processes taking place simultaneously both on the periosteal and intramedullary surfaces of the bone. In the second, the microscopic period (1836-1875), the physeal growth cartilage was discovered and described in detail, including its importance for the longitudinal growth of long bones. The first description of growth cartilage was published by a Swiss anatomist Miescher in 1836. Subsequently, this structure was studied by a number of English, German and French anatomists and surgeons. This whole period was concluded by Alfred Kölliker´s extensive study of bone resorption and its significance for typical bone shapes and Karl Langer´s study of the vascular supply of the growing and mature bone. CONCLUSION: Research by French, English, German and Swiss scientists between 1727 and 1875 yielded fundamental insights into the growth of long bones, most of which are still valid today.
Keywords: Osteology; History; Bone Development; vývoj kostí; History, 18th Century; Long bones; Physis; Animals; lidé; Bone growth; dějiny 18. století; Humans; zvířata; dějiny 19. století; History, 19th Century